Intercalation of tetracycline into layered clay mineral material for drug delivery purposes. (November 2014) - Aguzzi, C.; Cerezo, P.; Sandri, G.; Ferrari, F.; Rossi, S.; Bonferoni, C.; Caramella, C.; Viseras, C.
Abstract : Intercalation of tetracycline (TC) into a pharmaceutical grade layered clay mineral was carried out, and the resultant complex was characterised. The intercalation of TC into the interlayer space of the clay took place via cation exchange resulting in an increase in d spacing of the clay and changes in the spectral bands of the NH + vibration of the drug. Thermogravimetric analyses showed a delay in drug decomposition temperature as a consequence of drug intercalation. Release rate of the retained drug in simulated gingival fluid was compatible with the use of the complex in periodontal extended drug release systems.